EXAMPLES OF THE HISTORY OF THE MATERIAL CULTURE OF CHAGANIAN ARE THE PEARLS OF OUR SPIRITUALITY - Ergashev Mavlon Eshniyozovich (Scholar Express Journal, 2021)
The article provides a scientific analysis of the formation of the Chaganian state, theoretical and practical views on its development, discussions on this issue, the spiritual foundations of the first statehood, which is of particular importance in the history of Uzbek statehood
Keywords: Chaganiyan; museum; early Iron Age; Mirshodi